Factors Associated With Hospitalization or Intensive Care Admission in Children With COVID-19 in Latin America - López-Medina, Eduardo; Camacho-Moreno, German; Brizuela, Martin E.; Dávalos, Diana M.; Torres, Juan Pablo; Ulloa-Gutierrez, Rolando; López, Pio; Debbag, Roberto; Pérez, Paola; Patiño, Jaime; Norero, Ximena; Mariño, Cristina; et al. (Frontiers in Pediatrics, 2022)
Background: Limited data is available from low-middle and upper-middle income countries of the factors associated with hospitalization or admission to pediatric intensive care unit (PICU) for children with COVID-19. Objective: To describe the factors associated with hospitalization or PICU admission in a case-series of children with COVID-19 in Latin America. Method: Cases reported from 10 different Latin American counties to the Latin-American Society of Pediatric Infectious Diseases (SLIPE-COVID) research network from June 1, 2020, and February 28, 2021 were analyzed. Outpatient or hospitalized children <18 years of age with COVID-19 confirmed by polymerase chain reaction (PCR) or antigen detection (AgD) from the nasopharynx were included. Children with multisystem inflammatory syndrome in children (MIS-C) were excluded. Associations factors were assessed using univariate and multivariable logistic regression models. Results: A total of 1063 children with COVID-19 were included; 500 (47%) hospitalized, with 419 (84%) to the pediatric wards and 81 (16%) to the ICU. In multivariable analyses, age <1 year (Odds Ratio [OR] 1.78; 95% CI 1.08 to 2.94), native race (OR 5.40; 95% CI 2.13 to 13.69) and having a co-morbid condition (OR 5.3; 95% CI 3.10 to 9.15), were associated with hospitalization. Children with metabolic or endocrine disorders (OR 4.22; 95% CI 1.76 to 10.11), immune deficiency (1.91; 95% CI 1.05 to 3.49), preterm birth (OR 2.52; 95% CI 1.41 to 4.49), anemia at presentation (OR 2.34; 95% CI 1.28 to 4.27), radiological peribronchial wall thickening (OR 2.59; 95% CI 1.15 to 5.84) and hypoxia, altered mental status, seizures, or shock were more likely to require PICU admission. The presence of pharyngitis (OR 0.34; 95% CI 0.25 to 0.48); myalgia (OR 0.47; 95% CI 0.28-0.79) or diarrhea (OR 0.38; 0.21-0.67) were inversely associated with hospital admission. Conclusions: In this pediatric case series reported to the SLIPE research network in Latin America, young age, ethnicity, comorbidities and certain clinical and laboratory parameters were associated with higher rates of hospitalization. This evidence provides data for prioritization prevention and treatment strategies for children suffering from COVID-19.